A.SAIDOV, D. YAXYOYEVA INGLIZCHA-O‘ZBEKCHA-RUSCHA SOLIQ VA IQTISODIYOT ATAMALARI LUG‘ATINING LINGVISTIK TAHLILI - Ruzimov, Sh.S. (SCIENCE and SOCIETY, 2023)
In the article compiling principles of the English-Uzbek-Russian dictionary of tax and economic terms by A. Saidov, D. Yakhayoyeva were linguistically analyzed and recommendations aimed at its improvement were presented, showing its achievements and shortcomings with examples.
Keywords: tax; economics; affix; transcription; suffix; prefix; synonym; term